High-resolution serial sampling for nitrogen stable isotope analysis of archaeological mammal teeth. (May 2016) - Guiry, Eric J.; Hepburn, Joseph C.; Richards, Michael P.
Abstract: We present the results of an archaeological application of a rapid method for high-resolution stable nitrogen isotope (δ 15 N) measurements of time-series samples of tooth dentine. Over 250 analyses of samples of untreated dentine powder taken at continuous millimeter intervals along the growth axis of archaeological pig tusks were compared to results from a subset of tandem δ 15 N measurements of extracted and purified tooth collagen from the same teeth. Samples were also taken at 0.25 mm depth intervals to test the effect of depth with respect to temporal resolution of diet. Results show that δ 15 N measurements of untreated dentine powder from well-preserved archaeological teeth provide: 1) broadly comparable δ 15 N values to extracted and purified collagen, and 2) a rapid method of assessing dietary change over much shorter time intervals than is possible using extracted collagen. Analyses also show that large changes in δ 15 N values can occur across the thickness of a tooth due to the inclusion of multiple growth layers and/or secondary dentine, which results in a significant time−averaging lag in dietary representation, as demonstrated by samples that analyze collagen from the full width of the tooth wall. This method will also be useful for initial prescreening of samples to select for specimens of interest before undertaking further, more rigorous, sample pre−treatment and measurement. Highlights: A fast method for high-resolution sub-millimeter serial dentine sampling for δ 15 N analyses was tested. δ 15 N values from bulk powder and collagen from the same dentine are comparable. Sampling intervals lower than 1 mm provide a new level of temporal resolution for dietary analysis. Shallow sampling depth is critical for maintaining highest temporal resolution. Method is also an inexpensive way of prescreening bone and tooth samples for dietary analyses.